2015
DOI: 10.18632/oncoscience.160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of artesunate as a specific activator of ferroptosis in pancreatic cancer cells

Abstract: Oncogenic KRas reprograms pancreatic ductal adenocarcinoma (PDAC) cells to states which are highly resistant to apoptosis. Thus, a major preclinical goal is to identify effective strategies for killing PDAC cells. Artesunate (ART) is an anti-malarial that specifically induces programmed cell death in different cancer cell types, in a manner initiated by reactive oxygen species (ROS)-generation. In this study we demonstrate that ART specifically induced ROS- and lysosomal iron-dependent cell death in PDAC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
307
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(312 citation statements)
references
References 56 publications
(101 reference statements)
2
307
0
3
Order By: Relevance
“…Recent clinical trials indicated that the tumor suppression action of ART on advanced breast cancer, 14) colorectal cancer 15) and pancreatic cancer cells. 16) ART increasingly attracts the attention of cancer researchers due to a broad range of anti-cancer activity, such as pro-apoptosis attenuation of tumor growth, metastasis, and angiogenesis. 2,3,17) The present study further supported that ART could dose-dependently suppress tumor growth of prostatic tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials indicated that the tumor suppression action of ART on advanced breast cancer, 14) colorectal cancer 15) and pancreatic cancer cells. 16) ART increasingly attracts the attention of cancer researchers due to a broad range of anti-cancer activity, such as pro-apoptosis attenuation of tumor growth, metastasis, and angiogenesis. 2,3,17) The present study further supported that ART could dose-dependently suppress tumor growth of prostatic tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate selectively induces ferroptosis in K-Ras-mutant pancreatic ductal adenocarcinoma (PDAC) cell lines, but not human pancreatic ductal epithelial cells or wild-type K-Ras PDAC cells. 18 This process can be blocked by the iron chelator deferoxamine, whereas it is enhanced by exogenous lysosomal form of iron. 18 In addition to iron chelator deferoxamine, the ROS inhibitors (e.g., trolox and ferrostatin-1), but not necrostatin-1, significantly inhibit artesunate-induced ferroptosis in PDAC cells.…”
Section: Morphologymentioning
confidence: 99%
“…18 This process can be blocked by the iron chelator deferoxamine, whereas it is enhanced by exogenous lysosomal form of iron. 18 In addition to iron chelator deferoxamine, the ROS inhibitors (e.g., trolox and ferrostatin-1), but not necrostatin-1, significantly inhibit artesunate-induced ferroptosis in PDAC cells. 18 Another study shows that 10 artemisinin derivatives, including artesunate, altered numerous iron-related gene mRNA levels, which contributes to cell death in cancer cells.…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: ACSL4, acyl-CoA synthetase long-chain family member 4; CARS, cysteinyl tRNA synthetase; CBS, cystathionine-ÎČ-synthase; CGL, cystathionine-Îł-lyase; FTH1, ferritin heavy chain 1; GPX, glutathione peroxidase; GPX4, glutathione peroxidase 4; GSH, glutathione; G6PD, glucose-6-phosphate dehydrogenase; IPP, isopentenyl pyrophosphate; L-ROS, lipid-based reactive oxygen species; NADPH, nicotinamide adenine dinucleotide phosphate; NCOA4, nuclear receptor coactivator 4; NOX, NADPH oxidase; NRF2, nuclear factor E2-related factor 2; PGD, 6-phosphogluconate dehydrogenase; PUFAs, polyunsaturated fatty acids; RCD, regulated cell death; Sec, selenocysteine; Sec-tRNA [ (15,25,26). The metabolic peculiarities of ferroptosis vary among different types of cancer cell.…”
Section: Introductionmentioning
confidence: 99%